Environmental Performance of Ammonia Production in Indonesia using Life Cycle Assessment Approach - Muhammad Rizky Zen; Agus Adi Putra; Michelle Maria Magdalena Napitupulu; Chairunnisa Noviarini; Fano Alfian Ardyansyah; Cahaya Prautama (Universitas Diponegoro, 2024)
Ammonia is a fundamental component in fertilizer and chemical manufacturing processes around the world, but its production is a significant contributor to CO2 emissions in chemical industry. Implementation of carbon capture utilization and storage (CCUS) offers an alternative decarbonisation strategy to mitigate CO2 emissions in ammonia production. This study assesses the environmental performance of ammonia production through life cycle assessment (LCA) methodology. Environmental impacts are calculated using openLCA software with various impact assessment methods, including CML IA Baseline, Impact 2002+, Recipe 2016 Midpoint (H), and AWARE. The study scope encompasses the cradle-to-grave analysis, from the extraction of raw materials and transportation to ammonia production, main processes, distribution, and consumer product consumption, with a declared unit of 1-kg ammonia product. Our findings showed that CO2 removal and Power Plant in core processes in the core process as the most significant contributors to Global Warming Potential. Therefore, sensitivity analysis was conducted by reducing CO2 emission by 10% and 70% through CCUS implementation. The results showed that the CCUS implementation could reduce Global Warming Potential by up to 43%.